Effect of flooding on the survival of Leptosphaeria spp. in canola stubble. (24th January 2013) - Peluola, C.; Fernando, W. G. D.; Huvenaars, C.; Kutcher, H. R.; Lahlali, R.; Peng, G.
Abstract : This study used a versatile temperature‐control device to assess the effect of temperature (12–40°C) and duration (2–12 weeks) of flooding on the survival of Leptosphaeria spp. in canola ( Brassica napus ) stubble. Canola basal stems with blackleg symptoms were submerged in water in small glass jars containing 20 cm 3 soil on a thermogradient plate capable of simultaneously maintaining up to 96 independent temperature regimes. Flooded stems were sampled at 2‐week intervals, surface‐sterilized, and incubated on V8‐juice agar for 10 days to recover the pathogen. Flooding for 2 weeks substantially reduced pathogen recovery relative to non‐flooded controls and the pathogen was not recovered after 6 weeks of flooding, irrespective of temperature. The pathogen was eliminated slightly more rapidly at flooding temperatures >20°C than at 12–16°C. There was no difference between Leptosphaeria maculans and L. biglobosa in their ability to survive flooding. Stem tissues degraded most rapidly during the first 2 weeks of flooding, corresponding to a quick decline in pathogen survival during the same period. These results indicate that a paddy rice crop following winter rapeseed may minimize the impact of blackleg by eradicating the inoculum of Leptosphaeria spp. in stubble.